2019
DOI: 10.1186/s13019-019-0851-9
|View full text |Cite
|
Sign up to set email alerts
|

A graft inversion technique for retrograde type A aortic dissection after thoracic endovascular repair for type B aortic dissection

Abstract: BackgroundRetrograde type A aortic dissection (RTAD) is a rare but life-threatening complication after thoracic endovascular aortic repair (TEVAR) for type B aortic dissection (TBAD). A graft inversion technique was applied to distal anastomosis in total arch replacement for this complicated dissection. We reviewed our results of the processing for this serious complication. The aim is to evaluate the feasibility of this technology.MethodsFrom January 2013 to December 2017, 20 patients (80% male, mean age 50.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…19,20) In our study, the RTAD group did not increase the incidence of postoperative major adverse events compared with the no-RTAD group. Hu, et al 25) reported a graft inversion technique for distal anastomosis of RTAD. Compared with the traditional anastomosis technique, the inversion technique is beneficial to the exposure of the surgical field and can shorten the time of CPB.…”
Section: Discussionmentioning
confidence: 99%
“…19,20) In our study, the RTAD group did not increase the incidence of postoperative major adverse events compared with the no-RTAD group. Hu, et al 25) reported a graft inversion technique for distal anastomosis of RTAD. Compared with the traditional anastomosis technique, the inversion technique is beneficial to the exposure of the surgical field and can shorten the time of CPB.…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al [4] reported that the incidence of RTAD in TAAD was nearly 15%, while it was 1.3% to 8% in TBAD. [6,7] Several factors may contribute to these findings. First, the ascending aorta is subjected to high velocities and consequent shear stresses under pulsatile movements during the cardiac and respiratory cycles.…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to proximal leakage and rupture from repeated friction between the endograft and aortic wall. [4,6] Second, an increased radial force due to the curvature of the aortic arch and stent oversizing may injure the aortic wall. Third, blood pressure and heart rate instability can also increase the incidence of TAAD compared to TBAD; this is why TEVAR cannot be regularly used in the treatment of acute TAAD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations